How to Achieve Visualization of Obscure Drug Inhalation Stages in Inhalation Therapy? - Hiroyuki Ohbayashi (Disease and Health Research: New Insights Vol. 4, 2024)
The drug inhalation stage in inhalation therapy is crucial but often obscure. Information on how to inhale the drug is usually conveyed to the patient using ambiguous verbal expressions, such as “strongly,” “deeply,” and “slowly.” Patients typically determine the best method of drug inhalation based on their interpretation and understanding of verbal instructions. Consequently, direct intervention to provide optimal inhalation guidance for individual patients remains challenging, which can affect disease control. This has remained largely unexplored until now. The Tokico Inhalation Monitor TM (TIM) was developed to address the unpredictability of the drug inhalation stage. The TIM can simultaneously measure inhalation flow rate, duration, and total volume, displaying these metrics on the screen in real time. This chapter demonstrates how TIM can visualize obscure drug inhalation stages and illustrates the effects of inhalation instructions using this device.